Threads of Tradition: Silalahi Ulos Weaving and Cultural Significance in North Sumatra - Simbolon, Roma Sinta Br; Sihotang, Mujuranto; Tobing, Karisma (Jurnal Ilmu Pendidikan dan Humaniora, 2022)
Silalahi Ulos weaving, a distinctive cultural tradition in Silahisabungan District, Dairi Regency, North Sumatra, Indonesia, serves as a vibrant thread connecting the past and the present. This research delves into the rich cultural tapestry woven by the Batak Toba community, exploring the intricate patterns, motifs, and designs that adorn Silalahi Ulos textiles and their profound cultural significance. The study investigates the origins and historical development of Silalahi Ulos weaving, tracing its evolution from a traditional craft to an emblem of cultural identity. The research also highlights the rituals, ceremonies, and life events where Silalahi Ulos textiles play a pivotal role, symbolizing blessings, protection, and unity. The patterns and motifs found in these textiles, such as the Gorga, Naga, and Sigale-gale, convey deep spiritual and cultural meanings, serving as a bridge between the earthly and spiritual realms. This research further explores the challenges and threats faced by Silalahi Ulos weaving, including urbanization, changing lifestyles, and economic pressures. However, it underscores the resilience of the Batak Toba community in safeguarding their cultural heritage. Efforts to preserve, promote, and study Silalahi Ulos weaving encompass cultural education, economic sustainability through fair trade, intellectual property protection, interdisciplinary research, and community engagement. The conclusion reflects the commitment to preserving this unique cultural heritage, ensuring that Silalahi Ulos weaving remains a vibrant emblem of cultural pride and an enduring thread that weaves the cultural tapestry of Silahisabungan District, Dairi Regency, and Indonesia as a whole.